Tutor’s Strategies in Teaching TOEFL to Dompu Scholarship Hunter Community - Nur Wahyuni; Idhar Idhar; Arif Bulan (Universitas Sebelas Maret, 2022)
Test of English as a foreign language (TOEFL) is a test instrument to measure an individual skill level to English proficiency. Today, TOEFL is studied by almost students in Indonesia at the university level. The study aims to find out; (1) how are the tutor's strategies in teaching TOEFL to Dompu Scholarship Hunter Community, (2) what are the tutor's obstacles in teaching TOEFL to Dompu Scholarship Hunter Community, and (3) how are the tutor's efforts in solve the obstacles in teaching TOEFL to Dompu Scholarships Hunter Community. The research method was a qualitative research method with a qualitative descriptive approach. The data collection technique used structured interviews with three tutors. The findings were: (1) the tutor’s strategies were direct-learning, indirect learning, interactive learning, and independent learning, (2) inadequate time of learning per meeting, different basic abilities of students, and late distribution of TOEFL modules, (3) tutors provide TOEFL ebooks and additional assignments outside of class, and insert general material in each topic discussion.